An imBRICated international agenda: New ways and challenges of the Brazilian foreign policy in the XXI century - Fonseca, Marcela G. (2010)
The essay claims that Brazilian foreign policy, during the first decade of the 21st century, is more than ever, im“BRIC”ated. That is, Brazil’s foreign policy is immersed in a set of complex interactions with its new role as an emergent economic and political power. This complexity is made clear throughout the analysis of three major priorities of the Brazilian international agenda: the quest for a permanent seat at the United Nations Security Council, the leadership of South-South alliances and coalitions, and the priority of South-American integration. The authors argue that Brazil’s foreign policy decision-makers should be aware of the new complexities, and the challenges that they put forward for Brazil’s international actions, in particular for a Brazilian version of multilateralism.